Emerging radiotherapy technologies and trends in nasopharyngeal cancer. Issue 9 (3rd August 2020) - Tseng, Michelle; Ho, Francis; Leong, Yiat Horng; Wong, Lea Choung; Tham, Ivan WK; Cheo, Timothy; Lee, Anne WM
Abstract: Technology has always driven advances in radiotherapy treatment. In this review, we describe the main technological advances in radiotherapy over the past decades for the treatment of nasopharyngeal cancer (NPC) and highlight some of the pressing issues and challenges that remain. We aim to identify emerging trends in radiation medicine. These include advances in personalized medicine and advanced imaging modalities, standardization of planning and delineation, assessment of treatment response and adaptive re‐planning, impact of particle therapy, and role of artificial intelligence or automation in clinical care. In conclusion, we expect significant improvement in the therapeutic ratio of radiotherapy treatment for NPC over the next decade.